PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMBUATAN DAN PEMASARAN DOMER (DODOL MELINJO AREN) DI DESA PUSUK LESTARI KABUPATEN LOMBOK BARAT - Sari, Neti Kumala; Diniyatushoaliha, Ainun; Nurhidayat, Nurhidayat; Yusniati, Baiq Kayul Putri; Wulandari, Nur; Saputra, Hendra; Fathoni, Rohiana; Khadijah, Khadijah; Istiarini, Yunita; Reksi, Ni Kadek Dwi Okta Virana; Amrullah, Amrullah (Universitas Mataram, 2023)
Pusuk Lestari Village is one of the villages in Batu Layar District, West Lombok Regency. The majority of Pusuk Lestari Village residents work as traders and farmers. After conducting a survey, residents in Pusuk Lestari Village have abundant natural resources but a lack of processing skills is a problem in the village. It can be said that the people in the village are not able to take advantage of the abundant natural products, so it is necessary to take innovative steps that can be applied to optimize the community's skills in processing these natural resources through the KKN program with the Desapreneur theme. The Desapreneur theme is raised to increase the knowledge and skills of the community in optimally processing natural resources. One of the programs this time is by utilizing melinjo and palm sugar as raw materials for making dodol which will later provide benefits by increasing the income of the people of Pusuk Lestari Village. The stages of the Dodol Melinjo Aren Making Training are preparation of tools and materials, outreach, training, packaging, marketing, and evaluation. The results of the implementation of this training activity are increasing the knowledge and skills of the community so that they are able to continue the Dodol Making Training program. Several additional programs were also carried out, namely making tourist maps, teaching at school and teaching the Koran, clean village activities (PABERSA), and English courses.